Feasibility Study of an on-Grid Floating Solar PV Extension at the Lontar Coal-Fired Power Plant for Self-Consumption Using the SROI Method - Akbar, Muhammad Alfarisy; Arifin, Zainal (Empiricism Journal, 2026)
This study analyzes the technical, financial, and social feasibility of a 3 MWp on-grid Floating Solar Photovoltaic (FPV) extension planned for the ash pond area of the Banten 3 Lontar coal-fired power plant. The objective is to evaluate its contribution to reducing internal power consumption, assess economic performance, and estimate social benefits using the Social Return on Investment (SROI) approach. Methods include PVsyst simulation, financial analysis (NPV, IRR, Net B/C, Discounted Payback Period, and LCOE), and scenario-based SROI evaluation. Results show annual energy production of 4,590,668 kWh, contributing only 1.36% of total auxiliary demand, indicating a complementary role and implying that approximately 227 MWp would be required for full substitution. Financially, the project is infeasible, with a negative NPV, IRR below the 10% discount rate, Net B/C <1, LCOE higher than coal, and payback exceeding 25 years, based on assumptions including a 10% discount rate, Rp 786.88/kWh tariff, and CAPEX of $889.65/kWp. The SROI is 0.63 under the base scenario, increasing to 1.06 without coal subsidies and 1.29 with international carbon pricing, highlighting the importance of policy. This SROI represents an ex-ante evaluation of potential social value.